Legalitas Hak Tanggungan Elektronik dalam Pinjaman Online: Analisis Kewajiban Pembayaran Utang Berbasis Digital pada Sektor Agraria - Johamran Pransisto (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study discusses the legality and executive power of electronic mortgage rights in online loan transactions based on land collateral in the agrarian sector. This study analyzes related laws, doctrines, and practices using normative legal methods to identify legal protection and certainty of debt repayment obligations in the digital ecosystem. The results of the study indicate that although the Electronic Mortgage Rights (HT-el) system provides efficiency and ease of administration, there are still challenges in the form of security gaps, uncertainty of the legal status of electronic documents, and weak protection for debtors and creditors, especially on illegal online loan platforms. Therefore, it is necessary to improve regulations, strengthen digital infrastructure, and increase legal literacy so that digital transformation in the agrarian sector can run optimally while still ensuring legal certainty and protection of the rights of all parties.